2010
DOI: 10.1093/abbs/gmq012
|View full text |Cite
|
Sign up to set email alerts
|

MG132, a proteasome inhibitor, attenuates pressure-overload-induced cardiac hypertrophy in rats by modulation of mitogen-activated protein kinase signals

Abstract: Proteasome inhibitors are involved in cell cycle control, growth and inflammatory signaling, and transcriptional regulation of mitotic cells. A recent study has suggested that specific proteasome inhibitor MG132 may suppress cardiomyocyte hypertrophy in vitro. However, the underlying molecular mechanisms are not clear. In this study, we investigated the effects of long-term MG132 treatment on cardiac hypertrophy and the related molecular mechanisms in vivo. MG132 (0.1 mg/kg/day) was intraperitoneally injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…The results are in concordance with a number of studies on LVH remodeling in both mice and humans (33,49,63), in aging hearts (8), and ischemia-reperfusion injury (21,60) but is in discordance with other studies (5,12,20,32,45,46). The explanations for the varying responses in the LV have been debated (31,43) and may be related to differences in the animal models or in techniques used in assessing proteasome activity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The results are in concordance with a number of studies on LVH remodeling in both mice and humans (33,49,63), in aging hearts (8), and ischemia-reperfusion injury (21,60) but is in discordance with other studies (5,12,20,32,45,46). The explanations for the varying responses in the LV have been debated (31,43) and may be related to differences in the animal models or in techniques used in assessing proteasome activity.…”
Section: Discussionsupporting
confidence: 79%
“…However, studies have been contradictory, showing either increased or decreased proteasomal enzyme activity in the afterload stressed LV (31, 43). Other models have demonstrated both cardioprotective (9, 21, 25, 59) and cardiotoxic (12,20,27,32,45,46) roles of the UPS via regulation of apoptosis, NF-B signaling, and oxidative stress.Although much is known about the molecular mechanisms of LVH and LV failure (LVF), the mechanisms underlying right ventricular (RV) hypertrophy (RVH) and RV failure (RVF) are less understood. RVH and RVF are a major cause of morbidity and mortality in patients with pulmonary hypertension and represent long-term risks for patients with surgically corrected congenital heart diseases such as tetralogy of Fallot, L-transposition of the great arteries, and hypoplastic left heart (4, 34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that [19] in experimental inflammatory bo wel disease MG-132 in vivo reduced T cell-mediated intestinal inflammation but significantly suppressed cell migration and epithelial cell proliferation. MG-132 also has an influence on the cardiovascular system [8,29,34]. In a low dose (0.1 mg/kg) MG-132 administered intraperitoneally once per day even for 2 or 8 weeks may effectively prevent cardiac remodelling and dysfunction in pressure-overloaded hearts without marked drug toxicity [29].…”
Section: Systemic Administration Of Proteasome Inhibitionmentioning
confidence: 99%
“…The heart tissue was cut into 5 mm sections, and stained with hematoxylin and eosin (HE). Cardiomyocytes cross-sectional area was determined using the method described by Chen et al [16]. Cardiomyocytes size from each group was evaluated by measuring the cross-sectional area of cells using the image analysis system (CIAS-1000, China Daheng Group, Inc., Beijing, China).…”
Section: Morphologic and Hemodynamic Analysismentioning
confidence: 99%